I Need Out Because He Wants in the House: the Subject Pronoun in Need and Want Phrasal Constructions. - Paules, Gregory (My University, 2009)
In this project, which is part of a larger project examining syntactic, semantic, and pragmatic factors affecting want + prepositional adverb/phrase and need + prepositional adverb/phrase, we explore the role that one syntactic factor, namely subject type, plays in the widespread distribution of these constructions in written sources.
Color poster with text, map, and charts.
Keywords: Need (The English word); Want (The English word); English language--Pronoun; English language--Noun phrase; Posters